INFORMATION SEEKING BEHAVIOUR OF PROFESSORS AND STUDENTS OF ALLAHABAD UNIVERSITY AND ALIGARH MUSLIM UNIVERSITY: A COMPARATIVE STUDY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Information seeking behaviour is defined as a human habit that involves searching for information in a deliberate manner in order to fill a gap. This conduct might be difficult to define at times. As a user, professors and students, university libraries are the first place they look for information. The primary goal of this research is to look at the information requirements and behaviour of students and professors at Allahabad University and Aligarh Muslim University. The data for this study was gathered using a well-structured questionnaire from 50 Professors and 150 pupils. The study focuses on a variety of characteristics of their techniques and behaviour while looking for information, as well as barriers for collecting their requirements, the purpose and frequency of library visits, user satisfaction, and library services.